2007
DOI: 10.1091/mbc.e07-06-0582
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Fluxes of Focal Adhesion Proteins in Response to Cell Migration and Mechanical Signals

Abstract: Recent studies suggest that mechanical signals mediated by the extracellular matrix play an essential role in various physiological and pathological processes; yet, how cells respond to mechanical stimuli remains elusive. Using live cell fluorescence imaging, we found that actin filaments, in association with a number of focal adhesion proteins, including zyxin and vasodilator-stimulated phosphoprotein, undergo retrograde fluxes at focal adhesions in the lamella region. This flux is inversely related to cell m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 65 publications
9
81
0
Order By: Relevance
“…However, no study has so far reported the formation of an adhesion contact triggered by pure mechanical friction of actin filaments along the plasma membrane. Instead, recent studies have shown the different levels of dynamic correlation between integrins, FA-related proteins such as vinculin and talin, and actin filaments (Guo and Wang, 2007;Brown et al, 2006;Hu et al, 2007). The hierarchical organization of FAs therefore constitutes a differential 'slippage-clutch' mechanism (Wang, 2007), which transmits forces from actin motion to the extracellular matrix to promote cell migration (Hu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, no study has so far reported the formation of an adhesion contact triggered by pure mechanical friction of actin filaments along the plasma membrane. Instead, recent studies have shown the different levels of dynamic correlation between integrins, FA-related proteins such as vinculin and talin, and actin filaments (Guo and Wang, 2007;Brown et al, 2006;Hu et al, 2007). The hierarchical organization of FAs therefore constitutes a differential 'slippage-clutch' mechanism (Wang, 2007), which transmits forces from actin motion to the extracellular matrix to promote cell migration (Hu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…FAs incorporate a large number and diversity of compounds (Zaidel-bar et al, 2007), thus the precise description of force sensing and transmission in FAs is a great challenge. They assemble or reorganize directionally in response to external forces, as shown by single cell manipulation with micropipettes (Riveline et al, 2001;Guo and Wang, 2007), beads (Wang, 2007) or stretched substrates of adherent cells (Yoshigi et al, 2005;Kim-Kaneyama et al, 2005). Examples of mechanosensitive molecular mechanisms in FAs involve focal adhesion kinase (Mitra et al, 2005), paxillin in focal complexes (Zaidel-Bar et al, 2006) or the Src tyrosine kinase (Wang et al, 2005) and p130…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now clear that the molecules that comprise the clutch do not efficiently transmit all of the force to the substratum; but instead there is a molecular slippage (Brown et al 2006;Hu et al 2007). This is seen by the movement of adhesion molecules with actin during retrograde flow (Brown et al 2006;Guo et al 2007;Hu et al 2007). Some adhesion components like aactinin move with a velocity similar to actin, integrin generally does not move, and other components move at intermediate rates.…”
Section: Integrins In Cell Migrationmentioning
confidence: 99%
“…This phenomenon is known as retrograde flow. There is a balance between the actin cytoskeleton assembly and the retrograde flow that govern and control cell movement [1,27,54,20].…”
Section: Structural Components Of Cell-matrix Adhesionmentioning
confidence: 99%